2012
DOI: 10.1002/alr.21019
|View full text |Cite
|
Sign up to set email alerts
|

Changing paradigms in frontal sinus cerebrospinal fluid leak repair

Abstract: Frontal sinus CSF leaks were successfully closed in 97.3% of individuals. Our data supports the routine use of endoscopic repair in the treatment algorithm for frontal sinus skull-base defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 18 publications
3
76
0
1
Order By: Relevance
“…Hence, the follow-up requirements are more or less similar for both the approaches used for frontal sinus defect. The feasibility of repair of posterior table defects were nicely studied in cadaver by Eloy et al 15 and Batra et al 16 Few reports of repair similar defects has been reported earlier in literature by authors like Anverali et al, 2 Jones et al 14 and Eloy et al 6 Basing on this, we attempted the repair of the defect using endoscopic technique in this case along with resection of the mucocele and could find that there was no technical difficulty in the feasibility in repairing the posterior table defect.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hence, the follow-up requirements are more or less similar for both the approaches used for frontal sinus defect. The feasibility of repair of posterior table defects were nicely studied in cadaver by Eloy et al 15 and Batra et al 16 Few reports of repair similar defects has been reported earlier in literature by authors like Anverali et al, 2 Jones et al 14 and Eloy et al 6 Basing on this, we attempted the repair of the defect using endoscopic technique in this case along with resection of the mucocele and could find that there was no technical difficulty in the feasibility in repairing the posterior table defect.…”
Section: Discussionmentioning
confidence: 98%
“…The transnasal endoscopic approach for posterior table fractures is technically difficult procedures due to lack of proper instrumentation and due to lateral extension leading to lack of exposure for surgical work in the frontal sinus. 5,14 However, the endoscopic technique helps to avoid the morbidity of external approaches (e.g. coronal or brow incisions) and associated changes in cosmesis.…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al used this flap for resurfacing frontal defects, such as after cerebrospinal fluid leak, in 2012. 9 In a recent cadaver study, AlQahtani et al found that a posteriorly based nasoseptal flap could be used after the endoscopic modified Lothrop procedure. 10 The authors also described a laterally based nasoseptal flap for use during the endoscopic modified Lothrop procedure, and suggested that both posteriorly and laterally based flaps should be employed to cover both the anterior and posterior walls of the frontal sinus.…”
Section: Discussionmentioning
confidence: 99%
“…60,61 Despite this evolution, leak sites located at an extreme superior or lateral location within the sinus are beyond the reach of current instruments and should be approached by open techniques. 62 Generally, frontal sinus CSF leaks are anatomically located either within the frontal recess or within the posterior wall of the proper sinus. Shi and colleagues 63 recently described endoscopic approaches for specific leak site locations within the frontal sinus.…”
Section: Frontal Sinus Defectsmentioning
confidence: 99%